Cytokine single-nucleotide polymorphisms and risk of non-small-cell lung cancer. Issue 12 (December 2017) - Pérez-Ramírez, Cristina; Alnatsha, Ahmed; Cañadas-Garre, Marisa; Villar, Eduardo; Valdivia-Bautista, Javier; Faus-Dáder, María J.; Calleja-Hernández, Miguel Á.
Abstract : Objective: Lung cancer, particularly the non-small-cell lung cancer (NSCLC) subtype, is the leading cause of cancer-related death worldwide. Several functional polymorphisms in inflammatory cytokine genes, such as IL1B, IL6, IL12A, IL13 and IL16, have been associated with the risk of NSCLC. The aim of this study was to evaluate the association between ILs gene polymorphisms and the risk of developing NSCLC. Participants and methods: A retrospective case–control study was carried out, including 174 NSCLC cases and 298 controls of Spanish origin. IL1B (rs1143634), IL1B (rs12621220), IL1B (rs1143623), IL1B (rs16944), IL1B (rs1143627), IL12A (rs662959), IL13 (rs1881457), IL6 (rs1800795) and IL16 (rs7170924) gene polymorphisms were analysed by TaqMan. Results: The genotypic logistic regression model adjusted by smoking status showed that the IL1B rs1143634-TT genotype was associated with a lower risk of NSCLC ( P =0.04312; odds ratio=0.226; 95% confidence interval=0.044–0.840). No other gene polymorphisms showed an association with NSCLC in any of the models tested. Conclusion: In conclusion, IL1B rs1143634 was significantly associated with a higher risk of NSCLC. No influence of IL1B rs12621220, rs1143623, rs16944, rs1143627, IL12A rs662959, IL13 rs1881457 and IL16 rs7170924 on the risk of developing NSCLC was found in our study. Abstract : Supplemental Digital Content is available in the text.